The Daniel fast : feed your soul, strengthen your spirit, and renew your body - Gregory, Susan, 1950- (Tyndale House Publishers, 2010)
"Are you hungry for more of God in your life? Discover why millions of men and women throughout the world are rediscovering the ancient discipline of fasting--and, as a result, are encountering God in amazing ways. In this authoritative guide, Susan Gregory, 'The Daniel Fast Blogger' and an acknowledge expert on the popular partial fast inspired by the biblical book of Daniel, guides readers toward a successful fasting experience"--Cover, p. 4.